1981
DOI: 10.1099/00221287-127-2-351
|View full text |Cite
|
Sign up to set email alerts
|

The Invasion of HeLa Cells by Salmonella typhimurium: Reversible and Irreversible Bacterial Attachment and the Role of Bacterial Motility

Abstract: The interactions which brought about the invasion of HeLa cells by Salmonella typhimurium consisted of a sequence of three phases. Initially, the motility of the bacteria facilitated their contact with the HeLa cells whereupon the bacteria became attached in a reversible manner (i.e. the bacteria could be removed readily by washing the HeLa cell monolayers with Hanks' Balanced Salt solution). The binding forces responsible for reversible attachment were probably the weak long-range forces of the secondary mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(95 citation statements)
references
References 32 publications
6
89
0
Order By: Relevance
“…Earlier studies by Jones et al (1981) have shown that bacterial invasion in cell cultures may be divided into three phases: reversible adhesion, irreversible adhesion and invasion, each influenced by virus infection. One possibility is a change of electrical potential in the medium or the solution surrounding the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies by Jones et al (1981) have shown that bacterial invasion in cell cultures may be divided into three phases: reversible adhesion, irreversible adhesion and invasion, each influenced by virus infection. One possibility is a change of electrical potential in the medium or the solution surrounding the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Modulating flagellar activity in response to a variety of chemical and physical stimuli, single-celled micro-organisms can effectively search for optimal environmental conditions 1 . Flagellar motility also plays an important role in medicine, being a major contributing factor to pathogenicity and colonization in bacteria like Vibrio cholerae [2][3][4] . More recently, the possibility of exploiting swimming micro-organisms as actuators for microstructures has extended the interest for flagellar motility to the physical domain of micro-engineering applications [5][6][7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…This entry process resembles phagocytosis and results in intracellular bacteria enclosed within membrane-bound vacuoles. To study the molecular details of the initial entry process, in vitro assays have been developed for quantitating the ability of Salmonella to adhere to and enter cultured mammalian cells (7)(8)(9)(10)(11)(12)(13). Recent studies (14)(15)(16) have examined the interaction of Salmonella with epithelial cells that have formed polarized monolayers in vitro (17).…”
mentioning
confidence: 99%